The FinTech Dividend: How Much Money Is FinTech Likely to Mobilize for Sustainable Development? - Bryane Michael (ZBW – Leibniz Information Centre for Economics, 2020)
FinTech offers a new way to mobilize resources for all kinds of uses – including for funding sustainable development. Roughly 3%-13% of funding required for the UN's Sustainable Development Goals (SDGs)– or around 50 billion to 125 billion – could come from a `FinTech Dividend.' Such a dividend derives from the use of FinTech platforms to increase savings and investment (overall), channel resources into publicly funded as well as privately-funded SDG-related activities and policies, and encourage the use of internet platforms, which deliver novel goods and services that relate to the seventeen SDGs. Less than half of UN members have FinTech laws and policies – making FinTech a ripe area for right-regulating. Unfortunately, in areas like institutional reform – no amount of money can guarantee achieving the SDGs, without wider legal and administrative reforms. And no clear data about the exact policies needed to help grow an economy (or pay for SDG spending) serve as any guide. With total investment in FinTech stuck at around 150 billion to 200 billion – the hoped for deluge of FinTech dollars on SDG activities may remain a trickle for years to come.
Keywords: G23; O16; K24; F63; 330; FinTech Dividend; SDG funding; FinTech Law; #FinTech4SDGs